Occurrence of potentially toxic benthic marine dinoflagellate in Malaysia - Ng, Boon Koon; Usup, Gires (Penerbit Universiti Sains Malaysia, 2004)
Malaysia is one of the maritime countries affected by seafood poisoning events associated with toxins produced by marine dinoflagellates.